2019
DOI: 10.1002/adom.201901139
|View full text |Cite
|
Sign up to set email alerts
|

Optical Antennas for Wavelength Division Multiplexing in Visible Light Communications beyond the Étendue Limit

Abstract: This paper presents a novel fluorescent receiver for visible light communications that combines a broad field of view (FoV) with a significant gain, and simultaneously enables wavelength division multiplexing (WDM) for data communications. These characteristics are achieved by creating a receiver that includes a stack of two fluorescent optical antennas, each designed to receive a different part of the spectrum and create two separable communication channels. The device outperforms the theoretical étendue limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…An alternative system combined the fluorescent layer with conventional focusing optics 18 , while further designs included flexible nanostructured devices 19 , fibre-based devices 20 , and organic–inorganic hybrids 21 . Finally, further enhancement in data rates was achieved in a multilayer device combining fluorescent materials designed to absorb different wavelengths in a wavelength division multiplexing arrangement 22 .…”
Section: Introductionmentioning
confidence: 99%
“…An alternative system combined the fluorescent layer with conventional focusing optics 18 , while further designs included flexible nanostructured devices 19 , fibre-based devices 20 , and organic–inorganic hybrids 21 . Finally, further enhancement in data rates was achieved in a multilayer device combining fluorescent materials designed to absorb different wavelengths in a wavelength division multiplexing arrangement 22 .…”
Section: Introductionmentioning
confidence: 99%
“…[109] More recently, a wavelength division multiplexing (WDM) approach was engaged, by taking advantage of a two-fluorophore system with different absorption spectra to separate data transmitted with differing wavelengths, as shown in Figure 11b. [110] LSCs have also been utilized as diffusers at the transmitter end of a VLC network. [111]…”
Section: Free Space Optical Communicationsmentioning
confidence: 99%
“…Besides this dual functionality, this device could also operate in an optical relay mode, with the interesting possibility to establish a VLC connection between a transmitter and receiver which are not in direct line-of-sight. In a recent publication, Manousiadis et al [92] have demonstrated that the fluorescent antennas could be used to implement wavelength division multiplexing (WDM) VLC scenarios. They have combined two fluorescent antennas, each of which was absorbing a different part of the visible spectrum.…”
Section: Fluorescent Antennas For Visible Light Communicationsmentioning
confidence: 99%